2016
DOI: 10.1007/s10530-016-1094-5
|View full text |Cite
|
Sign up to set email alerts
|

Overland transport of recreational boats as a spreading vector of zebra mussel Dreissena polymorpha

Abstract: In aquatic ecosystems invasive species are among the most important threats to biodiversity worldwide. Understanding the dispersal mechanisms of aquatic invaders is very important for protection and management of vulnerable water bodies. Here we ask how recreational boats that are transported overland could contribute to the dispersal of invasive zebra mussels among lakes in Switzerland. Using a questionnaire sent to registered boat owners, we surveyed properties of transported boats and collected information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…The results support that dreissenids can disperse long distances into isolated lakes via the boat hullmediated introduction pathway. This is in accordance with the recorded dispersal of zebra mussels via several long-distance jumps (Wilson et al, 1999) and the reported dispersal via recreational boats in Ireland and Switzerland (De Ventura et al, 2016). The possibility to disperse implies that legislative regulation to clean, drain and dry boats (e.g., Clean Boating Act, 2008) and educational campaigns to stop the spread of dreissenids via boats hulls are important management tools to decrease the release of dreissenids into uninfested lakes.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results support that dreissenids can disperse long distances into isolated lakes via the boat hullmediated introduction pathway. This is in accordance with the recorded dispersal of zebra mussels via several long-distance jumps (Wilson et al, 1999) and the reported dispersal via recreational boats in Ireland and Switzerland (De Ventura et al, 2016). The possibility to disperse implies that legislative regulation to clean, drain and dry boats (e.g., Clean Boating Act, 2008) and educational campaigns to stop the spread of dreissenids via boats hulls are important management tools to decrease the release of dreissenids into uninfested lakes.…”
Section: Discussionsupporting
confidence: 86%
“…These vectors enable continued spread in an already colonized river basin as well as long-distance dispersal, including overland transport to isolated water bodies by water craft. In the case of the latter, recreational boats are among the main vectors (Buchan & Padilla, 1999;De Ventura et al, 2016). Several authors report introductions due to ballast water exchange (Johnson & Carlton 1996) and secondary spread due to discharge of water contained in boats (Johnson & Carlton, 1996), macrophytes attached to anchors, propellers or boat trailers (Johnson & Carlton, 1996;Johnson et al, 2001) or boat hulls Pollux et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector of within-watershed dispersal into area 3 remains unclear. Our findings suggest that international shipping is the main vector, but secondary vectors, such as recreational boating within and between waters (Johnson et al 2001;De Ventura et al 2016) or alternatively passive transport by water birds (e.g. Wood 2002;Figuerola and Green 2002;Charalambidou et al 2003;Reynolds et al 2015) or fish (Markovic et al 2009) may be potential vectors of dispersal of the species into new areas within the watercourse.…”
Section: Discussionmentioning
confidence: 76%
“…The limitation of native data could be attributed to dispersal or biotic interactions (Soberón and Peterson 2005); the difference in environments between native and global distributions is also termed niche unfilling (Guisan et al 2014). In our zebra mussel study, the major reason could be that the human mediated dispersal has greatly expanded the accessible area to zebra mussel (Griffiths et al 1991, Gallardo et al 2015, De Ventura et al 2016. Another reason for the relative narrowness of native occurrence data is adaptation of introduced populations to previously limiting conditions in the invaded range (Prentis et al 2008, Moran andAlexander 2014).…”
Section: Positive Effects Of Physiological Knowledge On Model Calibramentioning
confidence: 98%